The Roles of Academic Ability, Gender, and Grade Level in Pre-Service Teachers' Critical Thinking Skills at Ecology Course - Panggih Priyambodo; Wulandari Saputri; Risya Pramana Situmorang; Rini Rita T. Marpaung; Zalsa Nurlinda Apriyani; Handrianus Eka Uma (Journal of Science Education Research, 2026)
Pre-service teachers (PSTs) are expected to have the ability to engage in mitigating various ecological difficulties in the future thanks to their abilities in critical analysis. Critical thinking (CT) is influenced by various factors. However, not much in-depth research has been conducted on CT skills in previous studies. This study evaluated PSTs’ CT abilities based on GPA, gender, and grade level. In this quantitative descriptive research, 265 PSTs from various institutions in Java, Indonesia participated. An ecological essay test was used to collect data, and descriptive statistics and the Kruskal Wallis test were used to analyze the data. The results showed that PSTs' CT skills were in the medium category ( = 45.12), with the interpretation component getting the highest score ( = 51.64) and the inference aspect getting the lowest score ( = 33.96). The findings of this study also showed statistically significant differences in CT skills based on GPA, gender, and grade level. Better CT skills are found in PSTs who have a high GPA, are female, and are in 5th grade. This finding may have an impact on improving lecture programs so that PSTs' CT skills improve more effectively.